2013
DOI: 10.1371/journal.pone.0076356
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences: Examination of the 12-Item Bem Sex Role Inventory (BSRI-12) in an Older Brazilian Population

Abstract: ObjectivesAlthough gender is often acknowledged as a determinant of health, measuring its components, other than biological sex, is uncommon. The Bem Sex Role Inventory (BSRI) quantifies self-attribution of traits, indicative of gender roles. The BSRI has been used with participants across cultures and countries, but rarely in an older population in Brazil, as we have done in this study. Our primary objective was to determine whether the BSRI-12 can be used to explore gender in an older Brazilian population.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 37 publications
(59 reference statements)
3
56
1
2
Order By: Relevance
“…Fourth, as previously stated, we acknowledge that gender schemas have been through a significant shift since BSRI was put into use in the 1970s which presents challenges with respect to measuring gender identity in a valid way. However, recent studies provide evidence that the BSRI has been proven to be valid instrument (Carver et al, 2013;Vafaei et al, 2014). These limitations represent, in any case, opportunities to advance in our efforts to better understand business growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fourth, as previously stated, we acknowledge that gender schemas have been through a significant shift since BSRI was put into use in the 1970s which presents challenges with respect to measuring gender identity in a valid way. However, recent studies provide evidence that the BSRI has been proven to be valid instrument (Carver et al, 2013;Vafaei et al, 2014). These limitations represent, in any case, opportunities to advance in our efforts to better understand business growth.…”
Section: Discussionmentioning
confidence: 99%
“…The short BSRI contains six items for each masculine and feminine dimension. These items have been validated in previous research (Carver et al, 2013;Vafaei et al, 2014). Entrepreneurs rated the extent to which six masculine items (with leadership abilities, possessing strong personality, dominant, act like a leader, make decision easily, and defend own beliefs) and six feminine items (warm, gentle, affectionate, sympathetic, sensitive to others' needs, and tender) described themselves on a 7-point scale (1 = not at all like me, 7 = very much like me).…”
Section: Gender Identitymentioning
confidence: 99%
“…Better understanding of these issues will require addressing some limitations of the present study. First, though the BSRI continues to be widely used, it may not reflect the sociological transformation of gender roles since its inception in the mid-70s [3,13,25,28]. In particular, some authors have suggested a shift away from dichotomous male/female gender role characterization [3,16].…”
Section: Discussionmentioning
confidence: 99%
“…Using the BSRI situates this research within the large body of gender research that has used this inventory over the years (Carver et al, 2013;Hoffman and Borders, 2001).…”
Section: Content Analysismentioning
confidence: 99%